Pliensbachian/Toarcian boundary: the proposed GSSP of Peniche (Portugal) - Elmi, S. (2007)
The Peniche section (Portugal) is considered as a potential stratotype (GSSP) for the Pliensbachian/Toarcian boundary and it is analysed on the background of the available data on the ammonite successions from other Tethyan and NW European areas.